Effect of Dietary Chromium Supplementation on Growth Performance, Rumen Fermentation Characteristics and Some Blood Serum Units of Fattening Dairy Calves under Heat Stress - Soltan, M.A.; Almujalli, A.M.; Mandour, M.A.; Abeer, M. El-Shinway (Pakistan Journal of Nutrition, 2012)
Twenty four fattening dairy calves were assigned to investigate the effect of dietary Chromium (Cr) supplementation (0 or 3 mg Cr/head/day from organic preparation) on the growth performance and rumen fermentation characteristics as well as on some blood serum parameters under heat stress (35-40°C). Chromium supplementation significantly (p